Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1590/s1413-86702004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Toxoplasma gondii infection in women of childbearing age

Abstract: Objectives: Determine the risk factors involved in toxoplasmosis transmission and determine whether pregnancy is a risk factor for toxoplasmosis infection. Study design: Cross-sectional study carried out on 2,242 women at childbearing age. An indirect immunofluorescence reaction was used to identify immunity to Toxoplasma gondii. Previous gestations were also analyzed as a possible risk factor. The results were analyzed by χ χ χ χ χ² and OR tests, and by variance analysis. The sample was statistically balanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
59
2
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 20 publications
11
59
2
10
Order By: Relevance
“…Women who had been pregnant more than once presented a greater chance of infection by T. gondii (p = 0.0116). This result was similar to that observed by MITSUKA-BREGANÓ (2009) 41 6 , in Goiânia, Goiás, carried out a cohort study with women at fertile age and observed that the women previously pregnant were 1.7 times more likely of acquiring the infection than those who had never been pregnant before. It can be explained by the capacity of the mother´s immune response and the gestational period in which the woman is, and the virulence of the parasite strain 20 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Women who had been pregnant more than once presented a greater chance of infection by T. gondii (p = 0.0116). This result was similar to that observed by MITSUKA-BREGANÓ (2009) 41 6 , in Goiânia, Goiás, carried out a cohort study with women at fertile age and observed that the women previously pregnant were 1.7 times more likely of acquiring the infection than those who had never been pregnant before. It can be explained by the capacity of the mother´s immune response and the gestational period in which the woman is, and the virulence of the parasite strain 20 .…”
Section: Discussionsupporting
confidence: 89%
“…Contact with cats was also not associated to the chance of infection by T. gondii as reported in the studies by NASH et al (2005) 45 6 obtained an association to the presence of cats. In relation to living with cats, the possibility of parasite transmission by the act of touching is minimal or nonexistent.…”
Section: Discussionmentioning
confidence: 61%
“…Similar research in Brazil revealed that pregnant women with low level of income and education have higher risk to be infected by toxoplasmosis. 13 The same fact also reported by Avelino et al (2004) 14 that pregnant women in west area of Brazil with low level of education and income, had higher risk of toxoplasmosis infection. Lower level of education correlates with the level of knowledge and less healthy behavior.…”
supporting
confidence: 66%
“…Devido a alterações imunológicas e hormonais que ocorrem durante a gestação, as gestantes podem ficar mais vulneráveis ao parasita, assim, a gravidez pode ser considerada um fator de risco para a toxoplasmose 33 . Foi identificada uma associação entre o convívio com cães que ficam soltos na rua e a infecção por T. gondii, em vez de gatos, que apesar de ser surpreendente, achados semelhantes foram encontrados em Fortaleza, Ceará 15 .…”
Section: Discussionunclassified
“…Foi identificada uma associação entre o convívio com cães que ficam soltos na rua e a infecção por T. gondii, em vez de gatos, que apesar de ser surpreendente, achados semelhantes foram encontrados em Fortaleza, Ceará 15 . Os gatos podem disseminar oocistos no ambiente, enquanto os cães podem atuar como vetores mecânicos auxiliando na transmissão das formas infectantes do T. gondii aderidas em seu pelo 33,34 . Em outros estudos 13,19 o contato com gatos não teve associação significativa com a infecção pelo T. gondii.…”
Section: Discussionunclassified